Complete occlusion of the right middle cerebral artery associated with pneumonia - Ben Kang; Dong Hyun Kim; Young Jin Hong; Byong Kwan Son; Myung Kwan Lim; Yon Ho Choe; Young Se Kwon (Korean Pediatric Society, 2016)
We report a case of a 5-year-old girl who developed left hemiparesis and left facial palsy, 6 days after the initiation of fever and respiratory symptoms due to pneumonia. Chest radiography, conducted upon admission, showed pneumonic infiltration and pleural effusion in the left lung field. Brain magnetic resonance imaging showed acute ischemic infarction in the right middle cerebral artery territory. Brain magnetic resonance angiography and transfemoral cerebral angiography revealed complete occlusion of the right middle cerebral artery. Mycoplasma pneumoniae infection was identified by a 4-fold increase in IgG antibodies to M. pneumoniae between acute and convalescent sera by enzyme-linked immunosorbent assay. Fibrinogen and D-dimer levels were elevated, while laboratory exams in order to identify other predisposing factors of pediatric stroke were all negative. This is the first reported pediatric case in English literature of a M. pneumoniae-associated cerebral infarction involving complete occlusion of the right middle cerebral artery.